Values to work with in the class. Cinema and Civic education (Journal of Parents and Teachers, 2013)
Everyone knows that cinema has moralistic and transformative features. It is an educational resource with plenty of possibilities. In this subject, Civic education, cinema helps to explain abstract concepts such as tolerance, humiliation or friendship. Youngsters are consumers of experiences and so they must know and interpret them. This article presents a project divided in nine units and each unit has a film related to it to interpret and think through it.
Keywords: cinema and education; Civic education; values; youngsters.